Analisis Hubungan Panjang Lengan Terhadap Kemampuan Pukulan Atlet - Dody Tri Iwandana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine the factor analysis of arm length on the punching ability of boxing athletes in Bantul Regency. This research is a type of quantitative research. The method used in this study is the correlation method. The population of this study were boxing athletes in Bantul Regency, with a total sample of 12 athletes taken by total sampling. Data analysis used SPSS software version 25. There is a linear relationship between hitting ability and arm length with a significance value of 0.123 > 0.05. Based on the results of the study it can be concluded that there is a linear relationship between arm length and boxing athlete's punching ability. Keywords: Arm Length, Punching Ability, Boxing Athletes